การพัฒนารูปแบบการเรียนการสอนตามแนวคิดการพัฒนาด้านจิตพิสัย เพื่อสร้างเสริมสุขภาพนักเรียนระดับมัธยมศึกษาตอนต้น The Development of a Teaching – Learning Model Based on Affective Domain to Promote in Lower Secondary School Students’ Health - สรายุทธพิทักษ์ จินตนา (Journal of Education Studies, Chulalongkorn University, 2014)
การวิจัยนี้มีวัตถุประสงค์เพื่อ 1)พัฒนารูปแบบการเรียนการสอนตามแนวคิดการพัฒนาด้านจิตพิสัยเพื่อสร้างเสริมสุขภาพนักเรียนระดับมัธยมศึกษาตอนต้น 2) ประเมินประสิทธิผลของรูปแบบการเรียนการสอนที่พัฒนาขึ้น 3) ขยายผลการวิจัยให้รูปแบบใช้ได้กับการสอนสุขศึกษาระดับมัธยมศึกษาตอนต้นทั่วไป พัฒนารูปแบบโดยวิเคราะห์สังเคราะห์แนวคิดและข้อมูลที่เกี่ยวข้องเป็นรูปแบบฉบับร่าง ได้รับการตรวจสอบจากผู้ทรงคุณวุฒิและทดลองใช้เพื่อปรับปรุง ก่อนนำไปใช้ทดลองสอน10 สัปดาห์ ในโรงเรียนสาธิตจุฬาลงกรณ์มหาวิทยาลัยและโรงเรียนพุทธจักรวิทยา ผลการวิจัยพบว่า 1) รูปแบบที่พัฒนาขึ้นมีขั้นตอนการเรียนการสอน 8 ขั้น 2) กลุ่มทดลองทั้ง 2 โรงเรียน มีคะแนนเฉลี่ยทั้ง 3 ด้านหลังการทดลองสูงกว่าก่อนการทดลองและสูงกว่ากลุ่มควบคุมอย่างมีนัยสำคัญที่ระดับ .05 3) รูปแบบสามารถขยายผลให้ใช้ได้กับการสอนสุขศึกษาในระดับมัธยมศึกษาตอนต้นทั่วไป The objectives of this research were: 1) Develop a teaching learning model based on affective domain to promote in lower secondary school students’ health. 2) Find the effectiveness of the development model. 3) Extend the findings to health education teaching-learning in general lower secondary school students’ health. Develop model by analyzed and synthesized into a prepared model which received a critical review from experts. Then the model was brought to trial for improvement before experimenting 10 weeks in Chulalongkorn University Demonstration Secondary School and Buddhajakvittaya School. The results of this research were: 1) The developed model consisted of 8 teaching - learning steps, 2) The post-test mean scores of both experimental groups in 3 aspects were significantly higher than the pre-test and were significantly higher than those of the control groups at the .05 level of statistical difference, 3) The developed model can be extended generally to health education teaching-learning of lower secondary school students.